Single cell analysis of the adult neural stem cells of the lateral ventricle using a novel genetic marker - Nath, A (2019)
Canonically, adult neurogenesis occurs, in mammals, in two distinct regions of the brain—the subgranular zone of the dentate gyrus and the ventricular-subventricular zone (V-SVZ) of the lateral ventricle. The V-SVZ germinal niche is comprised, in part, by ependymal cells and the quiescent neural stem cells (NSCs) that lie near these cells. During neurogenesis, the quiescent NSCs change their transcriptional state and alter their cellular machinery to become activated NSCs. Together, quiescent and activated NSCs are also known as B-cells. B-cells generate transit amplifying cells, which then generate neuroblasts. Initially, it was believed that the function of V-SVZ neurogenesis was to populate the olfactory bulb with new neurons. However, recent work suggests that under disease and injury states it can lead to the formation of new striatal neurons. Studying B-cells is important because although they were identified two decades ago, many important questions regarding their development, specification, and function remain unanswered. The fate of B-cells is specified at the time of their formation during embryonic development. This work suggested that there existed many different subpopulations of B-cells—each fated to generate different types of neurons in the adult mouse brain. However, the mechanism by which the B-cells are apportioned to the different subgroups still remains a mystery. In this thesis, we demonstrate that a BAC-Penk-CRE transgenic line (which causes CRE expression in cells with an active pre-pro-Enkephalin promoter), generated in our lab and crossed to an appropriate reporter strain, labels a novel subgroup of B-cells, as well as previously identified subgroups of B-cells and neuroblasts. Using single-cell RNA sequencing, and other validation techniques, we show that this novel subgroup expresses the 5-Hydroxytryptamine Receptor 2C (5-HT2C receptor) and the prolactin receptor—which have been functionally correlated with B-cells, but B-cells expressing these receptors have never been captured and sequenced before. We also show that this novel subgroup expresses the KiR7.1 channel and the folate receptor. These findings are novel and exciting and will allow for the further study of the heterogeneity of B-cells and to investigate the many unanswered questions. Finally, not only have we been able to validate the RNAseq data, but we also show that in a partial progressive model of Parkinson’s disease, cells expressing the BAC-Penk-CRE reporter increase their proliferation and can be found in the striatal parenchyma. Thereby demonstrating the functional importance of this group of V-SVZ stem cells.